The role of a weakly coordinating thioether group in ligation controlled molecular self-assemblies and their inter-conversions in Ni(ii) complexes of l-methionine derived ligand. (1st July 2019) - Kumar, Rakesh; Mutreja, Vishal; Sharma, Gyaneshwar; Kumar, Sanjeev; Ali, Anzar; Mehta, S. K.; Venugopalan, P.; Kataria, Ramesh; Sahoo, Subash Chandra
Abstract : A series of Ni(ii ) complexes of an amino acid derived ligand (Salmet) has been synthesized, and characterized by various techniques including X-ray crystallography. Alkali ions K + /Na + direct the conversion of monomers to multi-nuclear complexes. Abstract : A series of Ni(ii ) complexes of anl -methionine derived reduced Schiff base ligand has been synthesized and their interconversions are investigated for the first time with the help of a variety of physico-chemical techniques. The different reactant/reagent conditions lead to mono- (1 ), di- (2a /2b ) and tri-nuclear (3a /3b ) Ni(ii ) complexes and they are unequivocally characterized by single crystal X-ray crystallography. Alkali ions K + /Na + can serve as efficient templates for the conversion of1 to tri-nuclear complexes3a /3b which are thermally stable at increased temperature of 70 °C, but amenable to dissociation to1 in the presence of strongly interacting 18-crown-6-ether.2a gets transformed to2b in DMF, in which the essential structural change is the incorporation of one DMF molecule to the coordination sphere of one of the Ni(ii ) centers with concomitant release of the coordinating thioether arm of the ligand.2a and2b can also be converted to a self-assembled complex (3a /3b ) by alkali metal salt addition at ambient temperature. Warming the solution to 70 °C disassembles the tri-nuclear complexes with a perceptible colour change and this cycle can be repeated several times. Additional evidence for the inter-conversion and retention of all the complex species in solution is clearly established by ESI-mass and UV-vis spectroscopy. Variable temperature magnetic analysis shows weak ferromagnetic and antiferromagnetic coupling for binuclear and self-assembled complexes, respectively.